A incidência do chiste, do cômico e do humor no problema da segregação: um estudo psicanalítico - Lucena, Lucas Pereira (2024)
The triad of laughter, comprising joke, comicality, and humor, was the subject of one of the first metapsychological investigations, in which each of these processes was thoroughly exposed in economic, dynamic, and topical terms. Accordingly, the factors necessary to perform each process were surmised, but Freud did not restrict himself to the psychic conditions and showed the presence of socio-cultural factors as decisive for the realization of laughter. This fact contributed to the conception of our study, which investigates the incidence of comicalness on segregation, a problem that became more evident in the current resurgence of hate speech. This is, therefore, a qualitative bibliographic study that starts from the theoretical body of Freudian-Lacanian psychoanalysis to investigate the incidence of comicalness in the issue of segregating the other. For this purpose, the main goal was to investigate how joke, comicality, and humor concern the social and political spheres regarding the segregation of figures of alterity. With this in mind, this study has as specific goals to conduct a metapsychological study on joke, comicality, and humor from the contributions of Freud and Lacan and understand the ways of expressing the phenomena of segregation in the social bond from the notion of alterity in psychoanalysis and investigate how joke, comicality, and humor are placed regarding the symbolization of the difference and its consequences for the production of places dedicated to figures of alterity. The premise is that psychoanalysis can help understand the subjective, social, and political aspects involved in the manifestations of comicalness and its potentials and limits—regarding the maintenance of and fight against the segregationist logic and hate speech — to produce questions and contribute to discussions about the place of comicalness in the conflicts that permeate the social bond.